Evaluation of peripheral basophil activation during exercise provocation test for desensitized patients - Kunizaki, Jun; Sugiura, Shiro; Sakai, Akira; Teshigawara, Miyuki; Makino, Atsushi; Takasato, Yoshihiro; Matsui, Teruaki; Kondo, Yasuto; Ito, Komei (Frontiers in Allergy, 2023)
Some food allergic patients who have undergone oral immunotherapy develop exercise-induced allergic reactions on desensitization (EIARDs). This study investigated basophil activation status during the exercise provocation test (EPT) performed to diagnose EIARD. EPT was performed on 20 participants, and in vivo basophil activation status was analyzed using activation markers CD203c and CD63. The results showed that there was no significant difference between EPT-positive and negative subjects for basophil activation status throughout EPT. Consequently, in vivo basophil activation after ingestion of the causative food may not be associated with EIARDs. New tests are desired for predicting EIARDs.